2021
DOI: 10.3389/fphar.2021.631402
|View full text |Cite
|
Sign up to set email alerts
|

Edible Bird’s Nest Supplementation Improves Male Reproductive Parameters of Sprague Dawley Rat

Abstract: Edible bird’s nest (EBN) is reported to have a positive in vitro proliferative effect and contain male reproductive hormones. Spermatogonia cells proliferate during spermatogenesis under male reproductive hormones stimulation that include testosterone, follicle-stimulating hormone (FSH), and luteinizing hormone (LH). Characterization of EBN through liquid chromatography-mass spectrometry (LCMS) has found testosterone as a base peak. Six types of amino acids, estradiol and sialic acid were among the major peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…These data indicate that supplementation of EBN 250 mg/kg to the prepubertal young has decreased testis and epididymal coefficients. This result contrasts with the supplementation of the EBN 250 mg/kg in the adult rats group, which did not cause any decrease in testis and epididymal coefficients (Jaffar et al, 2021).…”
Section: The Effect Of Wi-fi Exposure On Male Children Reproductive S...contrasting
confidence: 79%
See 3 more Smart Citations
“…These data indicate that supplementation of EBN 250 mg/kg to the prepubertal young has decreased testis and epididymal coefficients. This result contrasts with the supplementation of the EBN 250 mg/kg in the adult rats group, which did not cause any decrease in testis and epididymal coefficients (Jaffar et al, 2021).…”
Section: The Effect Of Wi-fi Exposure On Male Children Reproductive S...contrasting
confidence: 79%
“…The decrease in testis and epididymal organ coefficients following EBN supplementation to the young rats was likely due to estradiol (E2) hormone activity. This hormone was previously characterized to present in the EBN extract used in this study ( Jaffar et al, 2021 ). Several previous studies have reported an association between the administration of the hormone E2 on the development of the reproductive system of male rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Randomly ten fields from each slide (2 slides/sample) were observed by an experienced evaluator using a blind technique under a phase-contrast microscope (200 ×) (Nikon, Melville, NY, USA). The percentage of sperm motility was recorded based on the appearance of both progressive motile and non-progressive motile sperm (Jaffar et al 2021).…”
Section: Sperm Motilitymentioning
confidence: 99%